1998
DOI: 10.1093/annonc/9.suppl_5.s133
|View full text |Cite
|
Sign up to set email alerts
|

Long-term toxicity of the treatment of Hodgkin’s disease

Abstract: SummaryAt the present time, the majority of patients who develop Hodgkin's disease can be cured with radiotherapy and/or chemotherapy. A long follow up of cured patients has shown that the cumulative toxicity from treatment related complications rivals the mortality from Hodgkin's disease. In addition to late fatal complications, delayed adverse effects of therapy on the thyroid, reproductive system, and bones are burdens many patients have to bear. Future treatment regimens for Hodgkin's disease will be desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…We found that gender, age, length of time since diagnosis and cancer type affect the frequency and type of health effects experienced by long‐term cancer survivors. Other investigators have noted significant late morbidity in Hodgkin's disease survivors,26 as well as correlations between age and adverse effects 27. We also found a high preponderance of health effects in Hodgkin's disease survivors; despite their young age, they frequently reported heart problems (26.3%), thyroid problems (33.8%), arthritis/osteoporosis problems (14.4%) and lung problems (10%).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We found that gender, age, length of time since diagnosis and cancer type affect the frequency and type of health effects experienced by long‐term cancer survivors. Other investigators have noted significant late morbidity in Hodgkin's disease survivors,26 as well as correlations between age and adverse effects 27. We also found a high preponderance of health effects in Hodgkin's disease survivors; despite their young age, they frequently reported heart problems (26.3%), thyroid problems (33.8%), arthritis/osteoporosis problems (14.4%) and lung problems (10%).…”
Section: Discussionsupporting
confidence: 61%
“…Another study reported that 20% of ovarian cancer survivors had abdominal and gynecologic side effects and neurotoxicities 16. Others have reported on late effects in long‐term survivors of Hodgkin's disease including children 17, 18, 19, 20. Overall, the available studies tend to focus on relatively specific health questions, to pertain to individual cancer types and to have fairly brief follow‐up duration.…”
mentioning
confidence: 99%
“…Second malignant neoplasms affect up to 10% of these patients [11,48]. In addition to these potentially fatal late complications, these patients have to face delayed adverse effects of therapy on the thyroid, reproductive system, and skeleton [8].…”
Section: Hodgkin's Diseasementioning
confidence: 99%
“…1,2,5,13 Hodgkin lymphoma (HL) treatment historically entailed high-intensity irradiation and chemotherapy, which has resulted in diverse long-term complications. 14,15 DHS is seen in HL survivors up to 4 decades after mantle field irradiation, [16][17][18][19][20][21][22][23] which can damage neurological and muscular structures adjacent to lymph nodes of the axillae, chest, and neck. 24 Leydig cell damage is a complication in male HL survivors who have undergone chemotherapy with alkylating agents (eg, cyclophosphamide and procarbazine).…”
Section: Introductionmentioning
confidence: 99%